Centrolene daidaleum (Ruiz-Carranza & Lynch, 1991) (Anura, Centrolenidae): A glassfrog with primitive and derived combat behavior - Rojas-Runjaic, Fernando J. M.; Cabello, Pedro (Zootaxa, 2011)
Glassfrogs (family Centrolenidae) constitute a diverse Neotropical group of epiphyllous and arboreal anurans (Señaris & Ayarzagüena 2005; Guayasamin et al. 2009). They are commonly encountered on stream-side vegetation and many species may show high densities during their reproductive season, with numerous territorial males calling for mates in relative small areas (Señaris & Ayarzagüena 2005; Kubicki 2007; Delia et al. 2010). Territoriality of males in several glassfrog species occasionally implies combat behaviors. Combat behavior has been poorly documented in glassfrogs, mainly reported from anecdotal observations in just 11 species (McDiarmid & Adler 1974; Duellman & Savitzky 1976; Greer & Wells 1980; Jacobson 1985; Restrepo-Toro 1996; Bolívar et al. 1999; Savage 2002; Guayasamin & Barrio-Amorós 2005; Kubicki 2007; Delia et al. 2010).